Fatigue Life Analysis of Remanufactured Radial Rolling Bearing with the Replaced Loading Zone - L. Chen; D. T. Bu; Z. B. Feng; H. B. Liu (Journal of Engineering)
The replacement of the loading zone is not considered in the active calculation method on fatigue life of remanufactured bearings. In practical application, when the radial bearings are reinstalled after remanufacturing, it is required to replace the loading zone, which results in a large deviation between the calculated fatigue life according to the active calculation method and the actual life. In this paper, the fatigue life factors of radial bearings with different remanufacturing levels are calculated according to the actual application condition. The results of case studies show that with the improvement of the remanufacturing level, regardless of whether the loading zone is replaced or not, the remanufacturing bearing life factor is gradually increased and the maximum can reach 1. Considering the replacement of the loading zone, the life factors of remanufactured bearings with different fixed rings are also very different, among which the remanufacturing deviation of fixed outer-ring level II is the largest, reaching 11.3%. However, with the increase of the remanufacturing level, the deviation decreases gradually. The life factors by the method presented in this paper of remanufactured radial bearings with the replaced loading zone are significantly higher than those of the active calculation method. The research results of this paper provides a more accurate calculation scheme for the fatigue life of remanufactured radial rolling bearings, which is a supplement to the active calculation method and has important practical significance for the practice of bearing remanufacturing engineering.